2021
DOI: 10.1192/bjo.2021.718
|View full text |Cite
|
Sign up to set email alerts
|

Association of COVID 19 pandemic with new onset Obsessive-Compulsive Disorder (OCD) symptomology in the medical students – A cross sectional study

Abstract: AimsObsessive-Compulsive Disorder (OCD) is an anxiety disorder, which is the sixth largest contributor to non-fatal health loss globally. Coronavirus disease (COVID-19) pandemic, aside from its impact on physical health, has also had its effects on mental health. This study aimed to explore the frequency of new onset OCD symptomology in medical students amidst COVID-19 pandemic and its association with potential sociodemographic parameters.MethodThis cross-sectional study was conducted among medical students s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Other variables as predictors for OCD in the general population may also apply to university students: being single places people at 1.836 times increased risk of having OCD, the presence of an increase in sleep latency is an independent predictor for OCD, and a history of psychiatric comorbidity. Mazhar et al [ 39 ] observed that female medical students in junior preclinical years are more likely to suffer symptoms of OCD at increased rates in contrast to male students. Fears, depression, eating disorders, and other stress-inducing factors had a magnifying effect that contributed to increased OCD prevalence in students during the pandemic [ 37 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Other variables as predictors for OCD in the general population may also apply to university students: being single places people at 1.836 times increased risk of having OCD, the presence of an increase in sleep latency is an independent predictor for OCD, and a history of psychiatric comorbidity. Mazhar et al [ 39 ] observed that female medical students in junior preclinical years are more likely to suffer symptoms of OCD at increased rates in contrast to male students. Fears, depression, eating disorders, and other stress-inducing factors had a magnifying effect that contributed to increased OCD prevalence in students during the pandemic [ 37 ].…”
Section: Reviewmentioning
confidence: 99%
“…This review finds that the COVID-19 pandemic negatively affected the mental health of university students, and the following trends have been identified: (1) decreased mental health: these psychological trends include increased stress, anxiety, self-reported decreased well-being, constant worry, etc. [ 1 , 3 , 4 , 6 , 9 , 10 , 12 - 23 , 26 - 28 , 30 , 31 , 33 , 34 , 46 ]; (2) psychiatric trends include the presence of depression, substance abuse, and increased psychiatric morbidity, including an increase in OCD occurrence as well as suicidal ideation [ 1 , 16 - 19 , 23 , 24 , 26 , 28 , 30 - 37 , 39 , 41 , 42 , 48 ]; (3) disruption of the circadian cycle trends, sleep disorders, and insomnia [ 10 , 14 - 16 , 19 , 20 , 46 ]; (4) the disproportional detrimental effect of COVID-19 on female students in all areas reviewed [ 3 , 6 , 9 , 13 - 16 , 20 , 28 - 31 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that pandemic-related stress has effects on symptom exacerbation (Abba-Aji et al, 2020). Mazhar, Khaliq, & Arshad (2021) also reported results regarding sudden symptom onset. In this respect, OCD becomes a very important phenomenon in the context of the pandemic.…”
mentioning
confidence: 93%
“…Abba-Aji ve arkadaşları (2020), toplum temelli çalışmalarında katılımcıların %53,8'inin (n=2771), COVID-19 salgını sırasında ellerini yıkamakla ilgili katı kurallar hissetiktiklerini, %60,3'ünün (n=3111), OKB semptomlarının başladığını bildirmiştir. Mazhar, Khaliq ve Arshad (2021), bir başka çalışmada sağlık öğrencileri ile çalışmış; öğrencilerin %75'inin (n = 497) pandemi sırasında OKB skorunda kötüleşme yaşarken; %25'inin (n = 176) pandemi sırasında yeni başlayan OKB semptomolojisi geliştirdiğini raporlamışlardır.…”
unclassified